Enhancing the Ability to Recognize Fraction Numbers Through Context-Based Concrete Media in Grade V Slow Learners at a Public Elementary School - Asril, Asril; Purwanta, Edi (Journal of Innovation and Research in Primary Education, 2025)
Fraction concepts represent fundamental yet challenging mathematical domains in elementary education, with difficulties particularly pronounced among slow learners who constitute one-fifth of typical classrooms. Traditional pedagogical approaches emphasizing rote memorization have consistently demonstrated limitations in fostering deep conceptual understanding for students with IQ ranges of 70-89. This study investigates the effectiveness of contextual-based concrete media in enhancing fraction recognition abilities among fifth-grade slow learners through differentiated instructional approaches. Classroom Action Research employing Stringer's Look-Think-Act model was conducted across two cycles with 15 fifth-grade slow learners at State Elementary School 005 Sangkulirang, East Kutai Regency. Mixed methods combined qualitative observations of learning processes with quantitative analysis of formative test results. Data collection utilized observation sheets, pre-post achievement tests covering fraction recognition (½, ¼, ¾), and documentation. Success criteria required 75% of students achieving scores ≥70 (minimum mastery criteria). Progressive improvements occurred across intervention phases, with student mastery rates advancing from 20% baseline to 53.3% (Cycle I) to 100% (Cycle II). Class mean scores increased systematically from 51.3 to 69.3 to 77.3 respectively. Qualitative observations revealed transformation from passive confusion to active mathematical discourse, with enhanced student engagement and confidence in fraction-related tasks. Contextual-based concrete media significantly enhances fraction recognition among slow learners, achieving complete mastery through systematic integration of manipulative materials with authentic problem-solving contexts. The findings provide evidence-based pedagogical strategies for inclusive mathematics instruction that accommodates diverse cognitive profiles while maintaining academic rigor.